Cratons and Fold Belts of India - Sharma, Ram.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Cratons and Fold Belts of India, is a unique attempt at presenting geological characteristics and evolution of the fold belts and the cratonic areas of the Indian shield. The author has evaluated the different evolutionary models for each fold belt in light of all the currently available geological and geochronological informations that are clearly listed. Shortcomings, if any, of each model are stated and a viable geodynamic model is presented for each fold belt. The book is self-contained--it includes an introduction to the processes of mountain building, especially plate tectonics theory with its application to the evolution of the Himalaya as an illustrative example$1 (Bso that the reader can better appreciate the novel approach to the evolution of Proterozoic fold belts. The author eschews a detailed account of the fold belts for a clear description of all the concepts that go into building models. It is primarily written for graduate students, teachers and for those geoscientists who aspire to know all about the Indian shield.s
Precambrian Terrains and Mountain Building Processes -- Cratons of the Indian Shield -- The Young and Old Fold Belts -- Aravalli Mountain Belt -- Central Indian Fold Belts -- Singhbhum Fold Belt -- Eastern Ghats Mobile Belt -- Pandyan Mobile Belt.
Keywords: Geography; Geology; Mineralogy; Physical geography; Earth Sciences; Geology; Mineralogy; Physical Geography